Evaluation of neurological imaging after hematopoietic stem cell transplantation in adults - Sadri, Sevil; Polat, Burcu; Balık Aydın, Berrin; Koçar, Hakan; Gemici, Aliihsan; Beköz, Hüseyin Saffet; Sevindik, Ömür Gökmen; Sargın, Fatma Deniz (Yüzüncü Yıl University Faculty of Medicine, 2022)
To investigate the risk factors for, and the incidence of, structural abnormalities in brain imaging among hematopoetic stem cell transplant (HSCT) patients and to correlate these findings with physical examinations. This study retrospectively reviewed all post-HSCT brain imaging taken in the researchers’ center between 2014 and 2020. 87 of 627 transplant patients were imaged. 34.5% (n = 30) were female. Age at transplant ranged from 18 to 74 years (median: 45). The most common malignancies were acute myeloid leukemia (AML; n = 21; 24.1%), 51 (58.6%) patients received allogeneic transplantation, and 36 (41.4%) received autologous transplantation. The imaging techniques were dispersed as follows: magnetic resonance imaging (MRI): 83.9% (n = 73), brain computed tomography (CT): 37.9% (n = 33), diffusion MRI: 19.5% (n = 17). 39.1% of the radiological images were normal; 20.7% showed disease recurrence; and 14.9% detected ischemic gliotic lesions. According to the imaging results, there was a statistically s ignificant difference between age values (p = 0.013). Patients with PRES were younger than those with no pathologies in their imaging, while patients with infarcts and ischemic gliotic lesions were older than those with normal imaging (p = 0.001). Patien ts with disease recurrence were older than those with PRES but younger than those with infarctions (p = 0.001). Neurological complications are not uncommon in transplant cases. In managing transplantations, it should be remembered that the presence of radiologically positive findings, especially positives for cerebrovascular complications, can significantly reduce survival.
Keywords: Brain Imaging; Neurological Complications; Hematopoietic Stem Cell Transplantation; Cerebrova Scular Complications